The Geographic Information System Development for Selection of Green Open Space in Urban Densely Area - Fahrul Agus; Ramadiani Ramadiani; Muhamad Azhari; Sawung AW.; Wardana S.; Amelia A.; Kusnandar Kusnandar (LPPM INSTITUT TEKNOLOGI TELKOM PURWOKERTO, 2018)
Utilization of integrated Decision Support System and GIS as one of the intelligent computerized system can be used to help make decisions quickly, accurately, and consistently. This research aims to apply Simple Additive Weighting (SAW) and built application system with ArcGIS platform to determination of urban Green Open Space (GOS) location in densely populated area. The study was conducted in Samarinda City, used secondary data and obtained from the Sanitation and Gardening Agency. Data were collected by survey and interview with experts and using Waterfall Framework for software development method. The research has resulted the priority sequence of GOS location of densely area of Samarinda City. The first priority location is the location under Juanda Flyover Bridge. Research has also developed Web based GIS software application of GOS location determination using SAW technique.